2015
DOI: 10.5433/1679-0359.2015v36n6sup2p4277
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tension and oocyte density during in vitro maturation affect the in vitro fertilization of bovine oocytes

Abstract: Oocyte maturation is the key factor affecting the fertilization and embryonic development. Factors such as oocyte density and oxygen tension can directly influence the IMV. Thus, the objective of this study was to evaluate the effect of the association of oxygen tensions (5% or 20%) with different oocyte densities (1:10µl or 1:20µl) in the in vitro maturation (IVM) of bovine oocytes on maturation and fertilization rates, ROS production and antioxidant activity. Three experiments were performed with bovine oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The results indicated that 100% of immature oocytes were in the GV/MI stages, while 73.20 ± 2.29% of in vitro matured oocytes were in the MII stage. These data show that the in vitro maturation method is not totally efficient, in agreement with data reported by several authors …”
Section: Introductionsupporting
confidence: 92%
“…The results indicated that 100% of immature oocytes were in the GV/MI stages, while 73.20 ± 2.29% of in vitro matured oocytes were in the MII stage. These data show that the in vitro maturation method is not totally efficient, in agreement with data reported by several authors …”
Section: Introductionsupporting
confidence: 92%